Reliability of RT-qPCR Pooling Method for COVID-19 Detection in Various Cycle Threshold Values (Althea Medical Journal, 2023)
Background: Reverse Transcriptase Quantitative Real-time Polymerase Chain Reaction (RT-qPCR) is a standard method to detect SARS-CoV-2, the cause of COVID-19 disease, albeit expensive for some laboratory settings. The pooling test is widely used for large-scale screening to speed up the turn-around time and reduce the cost of the RT-qPCR. However, the pooling test involves mixing a certain number of specimens which theoretically increases the possibility of false-negative results. This study aimed to evaluate the accuracy of the pooling test compared with the non-pooling test in different Ct values as a surrogate for viral load.Methods: RT-qPCR was performed in three groups of samples: non-pooling (individual samples), pooling of 5 samples and 11 samples, with various ranges of Ct value in the respective group: x
Keywords: Cycle Threshold (Ct) value; COVID-19; pooling test; RT-qPCR